Fabrication, formation mechanism and properties of three-dimensional nanoporous titanium dealloyed in metallic powders. Issue 8 (2nd February 2017) - Zhang, Faming; Li, Ping; Yu, Jin; Wang, Lili; Saba, Farhad; Dai, Ge; He, Siyuan
Abstract: Abstract : We present a novel route to fabricate 3D nanoporous α-Ti foams by dealloying of TiCu master alloy in solid state using Mg powders. Pure open-cell nanoporous α-Ti foams are fabricated with BET surface area of 34.4 ± 0.8 m 2 /g and pore size in the range of 2–50 nm. The dealloying using powders is a solid state chemical reaction process to form Cu2 Mg phase and Ti/Mg nanocomposites. The constituent of Cu in the TiCu alloy was dissolved into Mg powders thanks to the kinetics of interface reaction and volume diffusion. The pore-forming mechanism is a solid-state interdiffusion process. The ligament coarsening is from 492 to 650 nm with increasing of the dealloying temperature. The hardness and elastic modulus in nanoporous α-Ti foam follow linear decay fit with ligament size increasing. Our results demonstrate a facile strategy for the fabrication of nanoporous Ti foams with novel nanostructures and tailored properties.